(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to the increase in fine dust caused by deepening air pollution, interest in the adverse effects of fine dust has increased. In this study, an experiment was conducted by applying a physical adsorption mechanism to the matrix to evaluate the properties of the microdust adsorption matrix. Density, absorption rate, fluidity, thermal conductivity, strength, and fine dust adsorption tests were conducted as test items for the evaluation of the physical properties of the matrix mixed with blast furnace slag-based powdered activated carbon. In this study, powdered activated carbon was used as a material for adsorbing fine dust. The results of the experiment for fabricating a fine dust adsorption matrix using powdered activated carbon are as follows. As the mixing ratio of powdered activated carbon increased, the density and absorption ratio tended to decrease and the absorption ratio increased. The flowability test showed a tendency to decrease as the mixing ratio of powdered activated carbon increased. As a result of the thermal conductivity test measurement, as the mixing ratio of powdered activated carbon increased, it decreased due to the increase of voids. As a result of the fine dust measurement, the higher the mixing ratio of powdered activated carbon was, the more the concentration tended to decrease due to the physical adsorption action. Compared to previous experiments using photocatalysts, it has been confirmed that overall performance such as strength has decreased, so a solution is needed.